Pesantren Ramadhan Virtual Pada Masa Pandemi Covid-19 Di SMP YPPSB Sangatta Utara Kutai Timur - Mubarok, Ramdanil; Nafsiyah, Faizatun (STAI Publisistik Thawalib Jakarta, 2022)
Educational institutions have their own way of responding to the Covid-19 pandemic in the month of Ramadhan, including in terms of increasing the practice of Ramadhan for their students, one of which is by implementing a virtual Ramadhan Islamic boarding school program. YPPSB Middle School, North Sangatta, East Kutai, is one of the schools that carry out virtual Ramadhan Islamic boarding school activities. The purpose of service is to motivate students to improve their practice in the month of Ramadhan. The implementation of the Ramadhan boarding school is carried out virtually by using a computer, the Google Meet application and the internet network. The result is that the implementation of the service runs smoothly, and the students are enthusiastic about participating in the Ramadhan boarding school by actively asking questions in the discussion and question and answer sessions. The material presented is about prayer, congregational prayer, and prayer priests. The moral material discusses morals to parents, teachers, and fellow human beings.